Effect of Energy Utilization and Financial Development on Economic Growth in Nigeria - Okoye, Lawrence U.; Omankhanlen, Alexander E.; Okoh, Johnson I.; Okorie, Uchechukwu E.; Ezeji, Felix N.; Ehikioya, Benjamin I.; Ezu, Gideon K. (International Journal of Energy Economics and Policy, 2021)
The necessity for rapid economic growth has not only been of great concern to global institutions and agencies but has continued to dominate discussions at major economic conferences at the national and international levels. There is an implicit assumption of positive correlation between economic growth, as measured by increase in national output, and the welfare of citizens, with the effect that governments seek to understand the real causes of output growth to aid formulation and implementation of policies that promote the welfare of their citizens. The depth of academic research in this area of knowledge is a further indication of its relevance to humanity. This study builds on existing body of knowledge on the subject by estimating the contributions of the financial and energy sectors to the Nigerian economy between 1981 and 2018. Using the estimation method of dynamic ordinary least squares (DOLS), the study reveals electricity consumption, inflation and financial development as positive predictors of growth while oil price and gross fixed capital are negative predictors. From the above findings, we conclude that robust financial and energy sectors are major influencers of growth and therefore suggest that adequate attention be given to development of these sectors through formulation and implementation of supportive policies. In addition, we see the necessity for a need assessment of the infrastructure needs of the real sector in order to ensure that infrastructure critical to its performance is identified and addressed through targeted investment. Keywords: Energy consumption, Financial development, Economic growth, Endogenous growth theory. JEL Classifications: C22, G21, O47, Q43 DOI: https://doi.org/10.32479/ijeep.10691